Micro-CT Evaluation of Taurodontism in a Deciduous Molar and a Permanent Molar: Case Reports - Burcu Nihan Yüksel; Kaan Orhan; Firdevs Tulga Öz (Cumhuriyet University, 2019)
Taurodontism is a morphological anomaly of teeth characterized with large pulp chambers and apically displaced pulpal floor.  The aim of this case report was to make a comparative evaluation by panoramic radiographies and 3D examinations to locate pulp chamber and root canal morphology of a primary mandibular first molar and the adaptation of root canal filling material of a permanent mandibular first molar, both diagnosed with taurodontism. In Case-1, a mandibular primary first molar was extracted due to physiological root resorption seen in the panoramic radiograph. The micro-CT (Bruker, SkyScan 1174, Belgium) examined the distance of the tooth a (distance between the lowest and the top point of the pulp chamber) and b (distance between the lowest point of the pulp chamber and the apical). The tooth was classified as mesotaurodont by the value of 52.91 obtained with the formula a/b x 100. In Case-2, the tooth was extracted because of the large periapical radiolucency observed in the radiography taken from the tooth which was admitted for pain and percussion tenderness. The calculation for subgroup could not be performed due to loss of the "a" value because of the cavity preparation. Although the root canal filling on the radiograph was found to be sufficient and long enough, an empty extra canal and insufficient wall adaptation of root canal filling were detected by micro-CT. Despite the fact that taurodontism can be diagnosed by 2D measurements, it is obvious that a 3-dimensional examination is necessary to obtain decisive data about the root canal cavity morphology especially for endodontic treatment and also to define prevalence and subgroups of anomalies. Although micro-CT is seen as a method that provides more detailed images, it is thought that it should be developed and supported with clinical studies in order to be valid and easy to use in clinical practice.